Antiapoptosis and Antifibrosis Effects of Qishen Granules on Heart Failure Rats via Hippo Pathway. (12th December 2019) - Zhang, Jian; Liu, Junjie; Gao, Sheng; Lin, Weili; Gao, Pengrong; Gao, Kuo; Zhang, Yili; Du, Kangjia; Yang, Xiaomin; Wang, Wei; Zhu, Ruixin; Wang, Yong
Abstract : Qishen granules (QSG) are a famous formula with cardioprotective properties to heart failure (HF). The aim of this study was to investigate the underlying mechanism of QSG on apoptosis and fibrosis in the treatment of HF. HF model was induced by left anterior descending artery ligation on Sprague-Dawley rats. Transcriptome analysis was used to investigate the regulatory pathways of QSG on HF. Interestingly, downregulated genes of QSG were significantly enriched in Hippo pathway which plays a crucial role in regulating cell apoptosis and proliferation. We found that QSG inhibited the expressions of proapoptotic key proteins P-53 and fibrosis-related proteins TGF- β 1, SMAD3, and CTGF. Further, we conducted research on the key proteins in the Hippo pathway upstream of CTGF and P-53. The results showed that MST1, P-MST1, P-LATS1, and RASSF1A that exert proapoptotic function were downregulated after QSG intervention. Similarly, P-YAP and P-TAZ, mediating self-degradation and apoptosis, were both observably decreased after QSG administration. Taken together, QSG are shown to be likely to exert cardioprotective effects by inhibiting the progression of apoptosis and fibrosis through Hippo pathway.